Revealing dynamics: The impact of minimum wage on inequality within Germany's regions - Mariya Afonina (Bielefeld University, Faculty of Business Administration and Economics, 2025)
This paper examines the impact of the statutory minimum wage introduction in Germany on within-region inequality. Utilizing SOEP data, we estimate the effects across population subgroups disaggregated by sex. Macro-level findings show that while the interquartile ratio did not change significantly overall, the interdecile and P25/P10 ratios declined by -9% and -5%, respectively. However, disaggregation by groups reveals opposite trends for men and women. For women, the effect on hourly wages is about -5% and statistically significant only in the first year after the reform. On the contrary, for men, it appears later, increases over time, and reaches -10% in 2019-2022.Individual-level analysis reveals that for men the effect is concentrated in the first quartile of wage distribution, with no significant reduction in working hours, contributing to a cumulative and statistically significant decline in inequality. For women, however, there are not only significant spillover effects-with the top quartile experiencing real hourly wage decline -but also a statistically significant reduction in contracted hours, especially for low-wage earners. Both of these factors contribute to the limited effects of policy on women, despite an initial rise in hourly wages at the lower end of the distribution.
urn:nbn:de:0070-pub-30060230
Keywords: J31; J68; R10; R23; 330; minimum wage; inequality; regional differences; SOEP; difference-in-difference